Kemampuan Literasi Membaca Fiksi melalui Soal Pilihan Ganda Model AKM Siswa Kelas IX SMP Negeri 2 Kota Bengkulu - Fatra, Qalbita; Trianto, Agus; Wulandari, Catur (Jurnal Korpus, 2025)
The aim of this research is to determine the fiction reading literacy abilities of class IX students at SMP Negeri 2 Bengkulu City through solving AKM model questions. This research method uses quantitative methods, with a population of all class IX students at SMP Negeri 2 Bengkulu City, totaling 393 students. Then, to determine the sample using a purposive sampling technique of 10% of the total population. This research instrument is a fiction reading literacy ability test using the AKM model with 45 questions in the form of an objective test. Data analysis was carried out using descriptive statistics. This research resulted in the discovery that literacy skills in reading fiction by class IX students of SMP Negeri 2 Bengkulu City were in the poor category with an average score of 45.41. When viewed based on the problem formulation consisting of aspects of reading literacy (1) finding information, getting an average score of 61.33 in the sufficient category, (2) interpreting and integrating, getting an average score of 67.14 in the sufficient category, evaluating and reflecting. with an average value of 7.77 which is in the very poor category.